SERS‐based detection of barcoded gold nanoparticle assemblies from within animal tissue. (15th October 2013) - Dey, Priyanka; Olds, William; Blakey, Idriss; Thurecht, Kristofer J.; Izake, Emad L.; Fredericks, Peter M.
<x xml:space="preserve">Abstract</x> We have explored the potential of deep Raman spectroscopy, specifically surface‐enhanced spatially offset Raman spectroscopy (SESORS), for non‐invasive detection from within animal tissue, by employing SERS‐barcoded nanoparticle (NP) assemblies as the diagnostic agent. This concept has been experimentally verified in a clinically‐relevant backscattered Raman system with an excitation line of 785 nm under ex vivo conditions. We have shown that our SORS system, with a fixed offset of 2–3 mm, offered sensitive probing of injected 2‐quinolinethiol‐barcoded NP assemblies through animal tissue containing both protein and lipid. In comparison with that of non‐aggregated SERS‐barcoded gold NPs, we have demonstrated that the tailored SERS‐barcoded aggregated NP assemblies have significantly higher detection sensitivity. We report that these NP assemblies can be readily detected at depths of 7–8 mm from within animal proteinaceous tissue with high signal‐to‐noise ratio. In addition, they could also be detected from beneath 1–2 mm of animal tissue with high lipid content, which generally poses a challenge because of high absorption of lipids in the near‐infrared region. We have also shown that the signal intensity and signal‐to‐noise ratio at a particular depth is a function of the SERS tag concentration used and that our SORS system has a 2‐quinolinethiol detection limit of 10−6 M. Higher detection depths may possibly be obtained with optimization of the NP assemblies, along with improvements in the instrumentation. Such NP assemblies offer prospects for in vivo, non‐invasive detection of tumours along with scope for incorporation of drugs and their targeted and controlled release at tumour sites. These diagnostic agents combined with drug delivery systems could serve as a 'theranostic agent', an integration of diagnostics and therapeutics into a single platform. Copyright © 2013 John Wiley & Sons, Ltd.